Specific interactions, structure and properties in segmented polyurethane elastomers (eXPRESS Polymer Letters, 2011)
Two sets of segmented polyurethane (PU) elastomers were prepared from 4,4'-methylenebis(phenyl isocyanate) (MDI), 1,4-butanediol (BD) and a polyester or a polyether polyol, respectively. The molecular mass of both polyols was 1000 g/mol. The stoichiometric ratio of isocyanate and hydroxyl groups was 1 and the polyol/total diol ratio changed from 0 to 1 in 0.1 steps. One step bulk polymerization was carried out in an internal mixer and the samples were compression molded for testing. The results proved that specific interactions determine the phase structure and properties of these materials. Crystallinity was approximately the same in the two types of polyurethanes and the amount of relaxing soft segments was also similar. The determination of interaction parameters from solvent absorption and differences in glass transition temperatures indicated stronger interaction between hard and soft segments in the polyester than in the polyether polyurethane. Larger transparency of the polyester PU indicated the formation of smaller dispersed particles of the hard phase. The larger number of smaller hard phase units led to the formation of more physical cross-links distributed more evenly in the polymer. These differences in the phase structure of the polymers resulted in stronger strain hardening tendency, larger strength and smaller deformations for the polyester than for the polyether polyurethane.